THE FORMATION OF TOLERANCE OF PROFESSIONAL FOREIGN LANGUAGE COMMUNICATION BY MEANS OF CROSS-CULTURAL BUSINESS GAMES AMONG STUDENTS OF SAMARA STATE UNIVERSITY OF ECONOMICS - Gennady V. Glukhov; Julia D. Ermakova; Lyubov V. Kapustina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article presents a proven program of formation of tolerance of professional foreign language communication by means of cross-cultural business games among students of Samara State University of Economics. Within this program there were formulated the key objectives: to identify the readiness conditions of students for effective business coordination in the multicultural environment and to provide the formation of tolerance of professional foreign language communication with cross-cultural business games in the educational process. The efficiency of the proposed program of formation of tolerance of professional foreign language communication confirmed the reliability of the experiment results and the positive dynamics in the level of formation of professional qualities that help to carry out professional activities more efficiently and to take into consideration the personal touches of business partners, cross-cultural differences and ethnic diversity. The emphasis is paid to the methodology for cross-cultural business games, for the role of the teacher and the students. The authors describe the preparation phase of the game, the implementation phase and the reflection one. There is an example of one of the cross-cultural business games. They consider the fact that after using cross-cultural business games in the learning process, students’ level of forceful wordings to the business partners and colleagues decreases. The tolerance to uncomfortable professional conditions appears. Adaptive capacity to business communication increases. The graduates have a value system which will determine their future career.